Overcoming negative emotional states in sports - Palaima, J. (Psichologija, 1963)
Often enough in sports strong athletes don’t perform to their full potential because they don’t know how to get over negative emotions, so they get off track, give up, or just lose to weaker challengers. The objective of the author’s study was to ascertain how athletes struggle with negative emotions based on their experience. The interviewees were 300 athletes and coaches of different athletic fields and achievement levels. The author tries to ascertain a) what was the specific negative emotional impact that manifested itself during sports, b) what methods are applied by athletes in order to overcome the negative emotions and eliminate their impact on the course of combat sports, and c) what kind of training and education conditioning help athletes develop the ability to overcome negative states after losing a match. The research results demonstrated that negative emotional states primarily manifest themselves when an athlete loses confidence; his tactical thinking dulls, he gets overly agitated, or the opposite, he gets apathetic and his will power diminishes. The effort that the athletes make to overcome the effects of negative emotional states are primarily associated with a) self-confidence restoration, b) retreat from unpleasant experiences and thoughts, c) ascertaining reasons a failed action, d) self-persuasion that despite the failure, it is necessary to make every effort to win, or at least do as little damage to your own team as possible. This article provides practical recommendations for coaches on how to develop athletes’ ability to handle their own negative emotions during combat sports.